Why do adolescents hurt themselves? - Guan, Teik Ee; Lau, Poh Li (Universiti Malaysia Sabah, 2016)
Self-hurt behaviour is a deliberate self-harming behaviour although it is not suicidal. Of late, this behaviour seems to have become more prevalent among adolescents. However, many of us still find it a taboo to discuss it publicly. It has become a phenomenon that a school counsellor needs to tackle daily. Self-hurt behaviour is common not only in the west, but also in the east, including Malaysia. Many people question why adolescents hurt themselves deliberately nowadays? What actually encourages them to do so? Don’t they feel pain? This conceptual paper explains the reasons behind the action based on studies done by Freud. Understanding what lies behind the action enables us to have a deeper understanding of why adolescents engage in self-hurt behaviour nowadays.